Estado inflamatorio, oxidante y proaterogénico en trastornos del metabolismo del hierro - Meroño, Tomás (2015)
Iron overload and deficiency were associated with increased risk of cardiovascular disease (CVD). However, the mechanisms involved and the clinical impact of such alterations are scarcely known. Moreover, the therapeutic potential of maintaining iron homeostasis over CVD risk factors has not been fully studied. The aim of this thesis was to evaluate the role of iron levels over biomarkers of inflammation, endothelial dysfunction and atherosclerosis in patients with iron overload and deficiency in comparison with healthy controls, and to assess the impact of their respective treatments. Indicators of glucose and lipoprotein metabolism, the activities of lipoprotein-associated enzymes, the chemical composition and functionality of isolated lipoproteins and biomarkers of inflammation and atherosclerosis were evaluated. Patients with iron metabolism alterations showed a proatherogenic lipoprotein profile with presence of modified and dysfunctional lipoproteins and a proinflammatory state with increased lipoprotein-associated phospholipase A2. Such alterations were corrected in response to the treatments of each condition. In conclusion, iron overload and deficiency are associated with metabolic alterations and a proinflammatory state which might enhance the development of atherosclerotic CVD.